Effects of Heat Stress on Estrus Expression and Pregnancy in Dairy Cows - Szilvia Szalai; Ákos Bodnár; Hedvig Fébel; Mikolt Bakony; Viktor Jurkovich (Animals, 2025)
This study investigated how environmental temperature affects estrus behavior and pregnancy rates in lactating dairy cows during induced estrus. We hypothesized that higher temperatures reduce estrus expression and pregnancy rates and influence hormone levels. Fifty-eight healthy, multiparous, ovulation-synchronized cows were studied under heat stress (summer) and non-stress (winter) conditions. Cows were assigned to G7G or OvSynch (OVS) hormone protocols. Blood samples collected on insemination day measured estradiol, LH, prolactin, insulin, and IGF-1 concentrations. Estrus signs and behaviors were also recorded. We found that during summer, daily maximum temperature–humidity Index (THI) values mostly exceeded 68, confirming the presence of heat stress. Estrus behaviors—especially standing and mounting—were significantly reduced under heat stress, occurring five to seven times more frequently in winter than in summer. Estrus detection rate was 86% in winter and 53% in summer. Pregnancy rates also declined sharply in summer (10%) compared to winter (39%), with all summer pregnancies in the G7G group. Hormonal analysis showed that estradiol levels remained consistent in the G7G group, while in the OVS group, it was significantly higher in winter than in summer. No significant seasonal differences were observed in the other hormones. Our findings indicate that heat stress impairs estrus expression and pregnancy rates in dairy cows. However, we conclude that the choice of hormone synchronization protocol (G7G) and the use of an automated estrus detection system may help to improve reproductive performance.